PERTANGGUNGJAWABAN PIDANA PERAWAT DALAM TURUT SERTA MELAKUKAN TINDAK PIDANA ABORSI BERSAMA BIDAN - Dinda Arimby Raihany (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Recently, abortion has become a very controversial problem where there are parties who agree and disagree with abortion. Abortion (termination) is an intentional pregnancy (abortus provocative). The purpose of this study is to discuss from a normative juridical perspective about how to act law and law that gives punishment to nurses who have abortions and the legal construction of the Criminal Code and Law No. 36 of 2009 concerning health which is related to abortion. Abortion is one of the serious problems, from the number of abortions that have increased from year to year in Indonesia. Abortions that often occur in Indonesia tend to be experienced by teenagers. Pre-age pregnancies that are right for uremaja can occur due to minus attention from parents in the family, and because of promiscuity. Abortion of a child or fetus results in the death of the child or fetus. Abortion (abortion) which is qualified as an act of crime or a crime can only be seen in the Criminal Code even though Law Number 36 of 2009 concerning Health also include punishment for acts of abortion. Exactly, every action which is also violent to children even violence causes the child to die is subject to get punishment.Keywords: Responsibility of Nurses, Abortion Crimes